Clistoabdominalis Skevington, 2001 (Diptera: Pipunculidae) of Colombia, with description of a new species and an updated key to males of the Neotropical species - Ramos-Pastrana, Yardany; Marques, Dayse Willkenia A.; Rafael, José Albertino (Zootaxa, 2023)
Clistoabdominalis Skevington, 2001 has a cosmopolitan distribution and is a poorly studied genus of big-headed flies (Pipunculidae) in the Neotropical Region, completely unknown in Colombia. A new species is described from protected areas and conflict territories of limited access in Colombia, namely Clistoabdominalis lucyae sp. nov. (type-locality: Parque Nacional Natural Tayrona). Clistoabdominalis spinitibialis (Hardy, 1954) is recorded for the first time in Colombia, and an amended diagnosis provided. Illustrations and a dichotomic key to the Neotropical species of Clistoabdominalis are also presented.